The man of the people : political dissent and the making of the American presidency - Green, Nathaniel C. (University Press of Kansas, 2020)
"The office of the presidency stands at the center of a contentious, and even violent, debate over what it means to be an American. Defying nearly every prediction, Donald Trump won the 2016 election by appealing to a vaguely-defined, "great" American past, boasting he would reinvigorate an emasculated American nation beleaguered by dangerous foreigners, duplicitous Washington elites, and an entrenched liberal establishment promoting gender equality and religious, racial, and ethnic diversity. Critics lambasted him for failing to act "presidential," claiming that his divisive rhetoric betrayed America's core values. At the base of this divided political landscape lies a shared belief that the presidency is the possession of the American people, and the site where fundamentally incompatible visions of American nationhood wage an ongoing battle. The Man of the People traces the origin of this battle, and the presidency's place at its center, during the first two decades of US history under the Constitution: an era whose historical nuance, and contemporary relevance, are often drowned out by its considerable (and considerably politicized) mythology. It argues that the American nation's polarized, president-centered political culture has a history-one that is inextricably connected to a political contentiousness Americans often bemoan, and a bellicose, belligerent, and exclusionary national vision that took shape during the country's earliest decades. Beginning with the public debate over whether to ratify the Constitution in 1787, and concluding with Andrew Jackson's presidency, Nathaniel Green draws upon the vast printed materials (especially newspapers) published during the era to explain how early Americans fought bitterly to give concrete meaning to the nascent and amorphous concept of "American" by responding to the words and actions of presidential incumbents in numerous ways, especially through acts of political dissent. Over time, Americans across partisan lines claimed that real Americans were not subjects, "savages," or slaves-and made the presidency the most conspicuous symbol of a vision of the American nation rooted in white supremacy, gender hierarchy, and a deep suspicion of anything deemed "foreign.""--